Il carisma della Venerabile Maria Bordoni e la teologia di Marcello Bordoni - Sguazzardo, Pierluigi (Rassegna di teologia, 2021)
This article means to expose a reading of Nicola Ciola's essay on the figure of Maria Bordoni. It illustrates the theological and spiritual portrait of the Venerable and of her brother, Father Marcello Bordoni, with special reference to the deep connection between Maria Bordoni's spiritual intuition, and the rigorous development of the theological thought of the great lateranense Christologian. (English)